Collector's edition innovative packaging and graphics - Tolley, Stuart (Thames & Hudson, 2014)
Collector's Edition is a celebration of the outstanding creative possibilities that print continues to offer in the age of the digital download. It is a global survey that brings together over 170 examples of innovative and inspired packaging from the worlds of music, book publishing and magazines that have been released as a collector's, limited or deluxe edition.